Prevalence of malnutrition in Indian preschool-age children: a survey of wasting and stunting in rural Tamil Nadu, 1983 - Steinhoff, M. C. (1986)
A cross-sectional survey of the nutritional status of 1223 preschool-age children was carried out in a development area in the southern Indian state of Tamil Nadu. Altogether, 45% of the children were underweight (low weight-for-age), 51% were stunted (low height-for-age), and 21% were wasted (low weight-for-height). The rates of severe malnutrition using any of these criteria were low, and only 9.6% of the children were both wasted and stunted. The nature of the malnutrition strongly depended on age group. Rates of stunting increased with age, reaching 63% in the fifth year of life, whereas rates of wasting peaked at 36% in the second year of life and declined to 14% in the fifth year. Surveys that are designed to produce information on stunting and wasting are important in the planning and evaluation of nutrition intervention programmes.